Strategy of pacemaker and electrode replacement for superior vena cava stenosis - Zheng, Zhi-Peng (J Int Med Res, 2021)
Cardiac implantable devices are commonly used for superior vena cava stenosis, but there have been few reports of electrode replacement in the stenosed superior vena cava. A 73-year-old man was diagnosed with second-degree type II atrioventricular block and a permanent dual-chamber, rate-modulated pacing pacemaker was implanted 10 years previously. Because of depletion of the pacemaker battery and an increase in the ventricular pacing threshold, replacement of the pacemaker and ventricular electrode was required. During the operation, we found that the patient had severe superior vena cava stenosis on angiography, and this caused obstruction when a common guidewire was used to pass through the superior vena cava. After attempting various methods, we successfully passed through the vascular stenosis with a super slide guidewire and a long sheath, and completed replacement of the pacemaker and ventricular electrode. We summarize the related literature of superior vena cava stenosis related to a cardiac implantable device, and discuss the replacement strategy of this complication and other treatment options.